A prospective study of women with ASCUS or LSIL pap smears at baseline and HPV E6/E7 mRNA positive: a 3-year follow-up. Issue 5 (21st February 2018) - Bruno, M. T.; Ferrara, M.; Fava, V.; Barrasso, G.; Panella, M. M.
Abstract: Human papillomavirus (HPV) testing is used in the triage of women with a borderline smear result. The efficiency of testing women with a low-grade squamous intraepithelial lesion (LSIL) and atypical squamous cells of undetermined significance (ASCUS) is less clear. For this reason we used a new HPV test that detects E6/E7 messenger RNA (mRNA), which might have a higher specificity. The objective of this prospective study was to assess whether HPV E6/E7 mRNA positivity in women with ASCUS and LSIL at baseline, is able to predict those women who have a high risk of developing a histological cervical intraepithelial neoplasia (CIN2) or worse lesion. We took into consideration the women's age and HPV DNA genotype and followed them up for 3 years. Cervical samples from women with high-risk HPV (HR-HPV) DNA-positive ASCUS ( n = 90) or LSIL ( n = 222) were tested for the presence of HR-HPV E6/E7 mRNA and the women were monitored for the development of histopathologically verified CIN2+. Thirteen patients with ASCUS and 17 with LSIL did not complete follow-up. All patients with LSIL and ASCUS, enrolled in this study, had confirmed lesions at the colposcopic examination. Follow-up was available for 312 women, 193 were positive in the HR-HPV DNA test and 93 had a HPV E6/E7 mRNA positive test. Finally, 22 women positive in the HPV DNA test for high-risk genotypes and with positive E6/E7 mRNA had a histologically confirmed CIN2+. Only two cases with negative HPV E6/E7 mRNA had CIN2+. The study shows that women positive in the HPV E6/E7 mRNA test have a greater risk of malignant progression of cervical lesions and therefore deserve greater attention and earlier check-ups.